(untitled) (Cadernos de Sociomuseologia, 2020)
Manoela Nascimento Souza Departamento de Museologia, Universidade Lusófona de Humanidades e Tecnologias Dissertação de Mestrado Msc. (2018) Abstract The present investigation have aims to reflect about the sensorial experience of the body on museological exhibitions. Because of the complexity of this investigation the research proposes the development of a museological scientific method, theoretical and practical, as a process of participant knowledge of the movement of the thought and the world itself. This method is called live method, because it is alive as the subject which studies and participatory because part of the look of experience and understanding of the movement and of the order of life. This method serves for the museologists researchers and for the subject that experience. In this way, the research seeks to understand the faces that compose the human body to propose a museological environment for the sensorial experience of the body in museum spaces. The museological environment proposed is the wine. The wine as a generator of artificials sensasions alllows the subject to reflection, and an integrated knowledge about himself and about the world. To understand the viability of wine as a museological environment, research accompanies a field survey in order to investigate the action of the wine on the subject. The field research was carried out in the Brazilian wine Miolo Wine Group. Key-words: Sociomuseology; sensorial experience; live method; body; wine.